Integration of Cultural Literacy in the Development of Listening Skills Teaching Materials in BIPA Learning - Ramadan Lazuardi, Dian; Nugroho, Agung (JPI: Jurnal Pustaka Indonesia, 2026)
Abstract This study aims to develop listening skills teaching materials in the Indonesian Language for Foreign Speakers (BIPA) course based on cultural literacy for seventh-semester students of the Indonesian Language and Literature Education Study Program at PGRI Silampari University in the 2025/2026 academic year. This study uses a Research and Development (R&D) approach with the ADDIE development model which includes the stages of analysis, design, development, implementation, and evaluation. Data collection techniques were carried out through interviews, questionnaires, and tests. Data analysis was carried out using the Aiken’s V formula to measure the level of validity, student response questionnaire analysis to measure practicality, and the N-gain test to determine the level of effectiveness of the teaching materials through a one-group pretest-posttest design. The results of the study showed that the developed listening skills teaching materials based on cultural literacy met the criteria of validity, practicality, and effectiveness. The results of expert validation showed an average value of 0.87 with a very valid category. The results of the practicality test showed a percentage of 85.83% in the small group test and 91.74% in the large group test with a very practical category. In addition, the results of the effectiveness test showed an increase in the average score of students from 40.64 in the pretest to 88.54 in the posttest with an N-gain value of 0.80 which is included in the high category and a percentage of 80.24% with effective criteria. Thus, the cultural literacy-based listening skills teaching materials are effectively used in learning the BIPA course to improve students’ listening skills.